An Analysis of Students’ Difficulties in Solving Algebraic Operation Problems: A Case Study of Grade VII Students at Secondary School - Nuraida, Ida (Al-Mufid, 2024)
This study investigates the difficulties encountered by Grade VII students in solving mathematical problems involving algebraic operations. Using a qualitative case study approach, data were collected through problem-solving tests and semi-structured interviews. Students' responses were analyzed and classified into three levels of problem-solving ability: high, moderate, and low. One student was selected from each category for in-depth analysis. The findings reveal that the high-ability student demonstrated a complete understanding of the problem-solving process, including problem interpretation, planning, execution, and review. The moderate-ability student showed partial mastery, with challenges in executing and reviewing the solution plan. Meanwhile, the low-ability student struggled at every stage due to limited conceptual understanding and procedural knowledge. This study highlights the necessity of tailored instructional strategies that address students’ varying levels of mathematical proficiency and foster deeper comprehension in algebraic thinking.